A Descriptive Review of Common Knowledge Construction Model Studies in Science Education: The Case of Türkiye - Tolunay Sezen; Ahmet Taşdere (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
This study aimed to examine Common Knowledge Construction Model (CKCM) studies published in Türkiye within the scope of science education by using descriptive content analysis. Articles and postgraduate theses published on CKCM between 2011-2022 were analyzed based on different parameters. Publication types, educational needs for publication, aims and focuses, studied science topics, contents, methods, data collection tools, samples/study groups, teaching techniques applied in the model, and the results of the studies were analyzed separately for these articles and theses. The delimitations in identifying the studies to be analyzed were as follows: I) the studies were published during the period to 2011-2022, II) the context was relevant to Türkiye, and III) the focus was CKCM in science education. As a result, 21 research articles and 16 postgraduate theses (8 master’s and 8 doctoral theses) were obtained. The fact that very few studies have been conducted on CKCM was cited as the most common educational need among the reviewed studies. Intervention studies have been widely conducted, and most studies have been carried out using experimental methods. Questionnaires and scales, as well as achievement tests, were most frequently used in the data collection processes. Predict-(Explain)-Observe-Explain (P(E)OE) and Conceptual Change Text (CCT) were the most frequently used teaching techniques within the scope of the CKCM. While the science subjects taught varied socio-scientific issues (SSIs), such as water pollution, greenhouse effects, and human-environment relations were found to be the most frequently taught science content. The obtained results were discussed by considering the similarities and differences between CKCM and other teaching models. Specific suggestions were provided based on the analyzed parameters.